2011
DOI: 10.2298/avb1103141t
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hoof diseases on the concentrations of some acute phase proteins and other variables of the protein profile in heifers

Abstract: The aim of this study was to evaluate the possible influence of hoof diseases in heifers on the concentrations of selected acute phase proteins and some other variables related to protein metabolism in the blood. In the evaluation we included 35 heifers of a low-land black spotted breed and its crossbreeds, with pathological clinical findings on the hoofs. Blood samples were collected once, when the clinical signs of the disease were obvious. Blood samples were analyzed for haptoglobin (Hp), serum amyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…Floor slipperiness and cow care quality are usually two factors that show significant correlation with lameness (27). This study corresponds with previous reported investigations (20,28,31) and indicates that various claw diseases may induce a systemic reaction and increased production of some acute phase proteins. Significantly higher concentrations of haptoglobin and serum amyloid A protein were found in groups with acute laminitis and sole ulcer compared with healthy animals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Floor slipperiness and cow care quality are usually two factors that show significant correlation with lameness (27). This study corresponds with previous reported investigations (20,28,31) and indicates that various claw diseases may induce a systemic reaction and increased production of some acute phase proteins. Significantly higher concentrations of haptoglobin and serum amyloid A protein were found in groups with acute laminitis and sole ulcer compared with healthy animals.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, only a few investigations have been published on the acute phase response in dairy cows with claw pathology. It is reported that claw diseases induce systemic acute phase response by elevation of certain acute phase proteins, as a result of tissue damage, pain and impaired homeostasis (20).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast Smith et al [227] found that specific claw disorders (pododermatitis septica, pododermatitis circumscripta, interdigital necrobacillosis and papillomatous digital dermatitis) were all related to increased concentrations of serum Hp which in the cases of pododermatitis septica and interdigital necrobacillosis showed reduction in Hp on treatment. The investigation by Tothova et al [228] of cattle with hoof disease including pododermatitis, laminitis, sole ulcer and digital dermatitis did show significant increases in Hp and SAA as well as fibrinogen in the cattle with hoof disease. The lack of a response in Hp in the study of Kujala et al [226] is possibly due to the small samples size used and possibly milder forms of lameness or hoof disease being included in the observed groups.…”
Section: 4mentioning
confidence: 85%
“…In horses, SAA is synthesized locally in the mammary gland and in joints, and the protein has been shown in normal colostrum and synovial fluid from horses with experimentally induced arthritis (MacDonald et al 1996, Jacobsen et al 2006b). Significant increases in the serum concentrations of Hp, SAA and Fbg were found by Tóthová et al (2011) in heifers suffering from hoof diseases (pododermatitis, laminitis, sole ulcer, and digital dermatitis). In turn, Laven et al (2004) did not find a correlation between the presence of an acute-phase response and the development of sole hemorrhages in postpartum first-lactation heifers.…”
Section: Discussionmentioning
confidence: 99%
“…The economic losses result from lower milk production, ill temper of animals, fertility problems, increased need to cull animals and costs for diagnosis and treatment. Many studies have shown to the presence of an acute-phase response associated with locomotor infections or inflammation (Jawor et al 2008, Smith et al 2010, Tóthová et al 2011. In horses, has been shown that APPs levels in synovial fluid can help distinguish infectious from non-infectious joint disease, and when synovial fluid APPs levels were measured sequentially in the same patient, levels reflected effect of treatment (Jacobsen et al 2006a).…”
Section: Discussionmentioning
confidence: 99%